Jig Design,Assembly Line Design And Work Station Design And Their Effect To Productivity - Saptari, Adi; Salleh, Mohd Rizal; Wong, Soon Lai (JJMIE, 2011)
This report discussed the effect of workstation design, assembly design,jig design and working posture on the assembly of plugs.Two different designs of jig (vertical and rectangular) and two sets of assembly line design (one and two operators)and two set of workstations design (sitting and standing) were studied to observe their effects to productivity.Design of Experiments 23 with two levels of each factor is used to conduct an experiment for obtaining the most productive jig and assembly line design.Two groups of workers were employed to assemble the plug in 8 different ways.Number of replication is 32 for each setting and total of electric plugs produced by each group is 256 units.The results shows that jig design have the most significant effect to the assembly time. Furthermore,the other factors: assembly design and workstation design are also show significant factors to assembly time.However,interaction combinations of two or three factors were not significant to assembly time.The most productive assembly line design which achieved the lowest assembly time is the combination of one operator, with rectangular jig and work station design sitting. Meanwhile the working posture of workstation design that provides the lowest RULA score was sitting position,it provided score 2 which is safe.